Radiotherapy and radiosensitization in breast cancer: Molecular targets and clinical applications. (January 2022) - Bhat, Vasudeva; Pellizzari, Sierra; Allan, Alison L.; Wong, Eugene; Lock, Michael; Brackstone, Muriel; Lohmann, Ana Elisa; Cescon, David W.; Parsyan, Armen
Graphical abstract: Highlights: Enhancing effects of radiotherapy by using radiosensitizing agents is a promising strategy in breast cancer treatment. Various drugs for breast cancer show properties of radiosensitizers in preclinical and early stage clinical studies. Biomarkers for radiosensitivity in breast cancer are lacking, despite a number of promising molecular targets. Abstract: Relatively poor survival outcomes are observed in advanced or metastatic breast cancer, where local control of the primary or metastatic disease may be achieved by surgical resection, local ablative and radiation therapies. Radioresistance, poses a major challenge in achieving durable oncologic outcomes, mandating development of novel management strategies. Although multimodality approaches that combine radiotherapy with chemotherapy, or systemic agents, are utilized for radiosensitization and treatment of various malignancies, this approach has not yet found its clinical application in breast cancer. Some agents for breast cancer treatment can serve as radiosensitizers, creating an opportunity to enhance effects of radiation while providing systemic disease control. Hence, combination of radiotherapy with radiosensitizing agents have the potential to improve oncologic outcomes in advanced or metastatic breast cancer. This review discusses molecular targets for radiosensitization and novel systemic agents that have potential for clinical use as radiosensitizers in breast cancer.